How does workplace harassment influence the employees' response in a deluxe hotel?. Issue 11 (10th September 2019) - Jung, Hyo Sun; Yoon, Hye Hyun
ABSTRACT: Recently, workplace harassment in the form of superiors abusing their power over subordinates has emerged as a social problem. In the deluxe hotel work environment, dealing with this issue starts by asking whether harassment by a superior has taken place – and if so, how it has influenced subordinates' responses. The purpose of this study was to measure the perception of workplace harassment among employees and to explain the relationships between workplace harassment and employee engagement, satisfaction, burnout, and turnover intent in deluxe hotels in South Korea. The results showed that verbal aggression had a significant negative effect on employee engagement, while isolation, disrespectful behavior, and physical aggression exacerbated employee burnout. In addition, employee engagement significantly enhanced job satisfaction, while burnout increased employees' turnover intent. Limitations and future research directions are also discussed.